1986
DOI: 10.1111/j.1471-4159.1986.tb00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acid Neurotransmitters in the Corticostriate Pathway: Studies Using Intracerebral Microdialysis In Vivo

Abstract: The concentration of extracellular excitatory amino acids in the striatum of conscious, unrestrained rats was measured using intracerebral microdialysis, during chemical stimulation of the striatum in intact and hemidecorticate animals. Chemical stimulation of the striatum with tityustoxin (0.1 microM) evoked a rise in dialysate concentration of glutamate (to 383% of basal) and aspartate (to 156% of basal), accompanied by a drop in glutamine (to 55% of basal). These changes showed significant attenuation after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
39
2

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 28 publications
9
39
2
Order By: Relevance
“…Another method that has been used to elucidate the neuronal contribution to extracellular amino-acid levels is the lesioning of specific glutamatergic or GABAergic pathways and measurement of basal extracellular glutamate or GABA levels, respectively, in the brain structures where the axons of these neurons terminate (Young and Bradford, 1986;Herrera-Marschitz et al, 1992;Campbell et al, 1993a). Indeed, significant decreases in extracellular glutamate and GABA levels in the denervated structures compared to the levels in intact structures have been found.…”
Section: Lesion Studiesmentioning
confidence: 97%
“…Another method that has been used to elucidate the neuronal contribution to extracellular amino-acid levels is the lesioning of specific glutamatergic or GABAergic pathways and measurement of basal extracellular glutamate or GABA levels, respectively, in the brain structures where the axons of these neurons terminate (Young and Bradford, 1986;Herrera-Marschitz et al, 1992;Campbell et al, 1993a). Indeed, significant decreases in extracellular glutamate and GABA levels in the denervated structures compared to the levels in intact structures have been found.…”
Section: Lesion Studiesmentioning
confidence: 97%
“…The nucleus accumbens, a forebrain structure known to subserve behaviors governed by natural reinforcers, receives excitatory glutamatergic input from prefrontal cortex, hippocampus, thalamus, and amygdala (McGeer et al, 1977;Walaas and Fonnum, 1979;Young and Bradford, 1986;Fuller et al, 1987;Robinson and Beart, 1988), as well as a major dopaminergic innervation from the ventral tegmental area (Lindvall and Bjorklund, 1978). These innervations converge on the dendritic spines of the medium spiny neurons that populate the nucleus accumbens (Totterdell and Smith, 1989;Sesack and Pickel, 1990;Smith and Bolam, 1990).…”
Section: Abstract: Glutamate; Plasticity; Striatum; Intracellular Simentioning
confidence: 99%
“…Glutamate and possibly aspartate are important excitatory transmitters in the cortical fibres innervating this region (McGeer et al, 1977;Fonnum et al, 198 1;Young and Bradford, 1986;Butcher and Hamberger, 1987), whereas the inhibitory amino acid y-aminobutyric acid (GABA) appears to be the major transmitter in the striatonigral and stnatopallidal pathways, as well as in certain intrinsic neurones (Schwarcz and Coyle, 1977;Fonnum et al, 1978;Ribak et al, 1979;Butcher and Hamberger, 1987). There are at least three different subtypes of excitatory amino acid receptor in the brain, characterised by their preferential activation by the agonists N-methyl-D-aspartate (NMDA), kainate, and quisqualate (Watkins and Evans, 198 1;McLennan, 1983), and autoradiographic studies have shown that all three subtypes are present in the stnatum (Cotman et al, 1987).…”
mentioning
confidence: 99%